The Impact of Education Curriculum Changes on Improving the Quality of Learning at SMAN 1 Sukadana, Ciamis Regency - Suwandari, Lilis; Kuswanda, Wawan; Riyanti, Rini; Rosmaya, Nenden; Munandar, Eri Arif (Universitas Muhammadiyah Ponorogo, 2025)
The transition from the 2013 Curriculum to the Merdeka Curriculum in Indonesia represents a significant shift in the educational landscape, aiming to provide greater flexibility and autonomy for schools to adapt teaching to student needs and local contexts. This study examines the impact of this curriculum change at SMAN 1 Sukadana, Ciamis Regency, focusing on its effects on pedagogical approaches, student engagement, and educational outcomes. A quantitative descriptive approach was employed, with data collected through questionnaires distributed to teachers and students. The findings indicate that the adoption of the Merdeka Curriculum has encouraged teachers to implement more innovative and interactive teaching methods, such as project-based and cooperative learning, which have significantly increased student engagement and motivation. However, challenges such as inadequate teacher readiness, resistance to new methodologies, and limited infrastructure were identified as key barriers to effective implementation. These findings align with Kotter's organizational change theory, emphasizing the importance of systematic support, continuous professional development, and collaboration among educators and school leadership to facilitate successful curriculum adoption. The study also applies constructivist learning theory and the ARCS motivation model, demonstrating that student-centered approaches enhance learning experiences and outcomes. Despite its contributions, the study acknowledges limitations in sample size and scope, suggesting the need for further longitudinal research to comprehensively assess the long-term impact of the Merdeka Curriculum across diverse educational settings. The findings provide valuable insights for policymakers and educators in refining curriculum strategies to better support teaching and learning processes.